REDUCING THE USE OF ANTIBIOTICS BY USING NATURAL MEDICINAL PLANTS IN MEAT FARM ANIMALS: A REVIEW - Adnan Shakor Ahmed Al-perkhdri (Journals Park Publishing, 2022)
The use of some chemical preservatives that have been proven to have side health effects has spread, in addition to the occurrence of some dangerous diseases such as poisoning or cancer. It was found that the use of nitrite compounds that produce nitrosamines is one of the causes of many diseases, especially cancer, as well as the ability of some microorganisms to Resistance to these substances by producing substances that inhibit or impede the action of chemical compounds used in food preservation and to reduce and eliminate the effectiveness of microorganisms as a method of food preservation Medicinal plants have been used in many areas of life... Many studies have been found that confirm that these plants are not used for collateral damage and their security field makes them used more widely in the fields of life, especially in the medical fields and in the treatment of many diseases, especially incurable diseases. Studies have increased in recent years towards the use of natural additives, including herbs and medicinal plants as food additives and antimicrobials, as they are of natural plant origin and are safe to use instead of chemical industrial additives, whose use in meat and its products has caused the concern of most consumers because of its negative effects on human health as it is the main cause of diseases carcinogenesis .Therefore, attention was directed towards studying the properties of these natural additives and their anti-microbial properties .
Keywords: antibiotics; meat; plants